2016
DOI: 10.4103/0972-124x.181243
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation to assess the efficacy of 5% sodium fluoride varnish and diode laser and their combined application in the treatment of dentin hypersensitivity

Abstract: Background:Dentin hypersensitivity (DH) is an age old complaint with a great number of treatment modalities, but none of these are totally effective till date. Lasers being one of the latest treatment options in periodontics, a study was conducted to test the efficacy of diode laser (DL) in DH alone and in comparison with 5% sodium fluoride (NaF) varnish.Aim:The aim of the present study was to compare the effectiveness of 5% topical NaF varnish and 980 nm gallium aluminum arsenide (GaAlAs) DL alone and combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Our research, as well as research by other authors ( 28 , 29 ), demonstrates that low-energy lasers, including GaAlAs diode laser with wavelengths between 780 and 980 nm, have an effect on nerve endings, thus eliminating sensitivity.…”
Section: Discussionsupporting
confidence: 75%
“…Our research, as well as research by other authors ( 28 , 29 ), demonstrates that low-energy lasers, including GaAlAs diode laser with wavelengths between 780 and 980 nm, have an effect on nerve endings, thus eliminating sensitivity.…”
Section: Discussionsupporting
confidence: 75%
“…A study conducted by Aghanashini et al [ 10 ] found that both DL and FV groups showed no significant difference up to 15 days. However, another study conducted by Suri et al [ 28 ] found FV showing better efficacy than lasers up to 24-h interval. However, in both these studies, as time progressed DL’s showed more efficiency than FV in reducing DH.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, diode laser with 970 nm wavelength was applied to the dentinal surface for 60 seconds, as these parameters were shown to yield greater therapeutic effects [ 29 31 ]. Continuous wave mode, rather than the pulsed mode, was used allowing easier scanning of the whole dentinal surface [ 30 ].…”
Section: Discussionmentioning
confidence: 99%